2020
DOI: 10.1101/2020.04.10.036087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rank-dependent social inheritance determines social network structure in a wild mammal population

Abstract: The structure of animal social networks influences survival and reproductive success, as well as pathogen and information transmission. However, the general mechanisms determining social structure remain unclear. Using data on 73,767 social interactions among wild spotted hyenas over 27 years, we show that a process of social inheritance determines how offspring relationships are formed and maintained. The relationships of offspring with other hyenas are similar to those of their mothers over up to six years, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…group hunts or collective border patrols) or may be more common among strongly bonded individuals, and thus merit further study. For example, co-traveling may play an important role in the vertical transmission of social relationships from mother to offspring [37]. Finally, hyenas are known to use long-distance vocalizations to recruit their clan-mates over large distances in contexts requiring collective action [25], so the role of communication in driving fission-fusion patterns also warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…group hunts or collective border patrols) or may be more common among strongly bonded individuals, and thus merit further study. For example, co-traveling may play an important role in the vertical transmission of social relationships from mother to offspring [37]. Finally, hyenas are known to use long-distance vocalizations to recruit their clan-mates over large distances in contexts requiring collective action [25], so the role of communication in driving fission-fusion patterns also warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…One example of a socially explicit ABM in the study of animal behaviour is the social inheritance model , in which offspring are likely to form connections with friends of their parents while avoiding parents’ enemies (Ilany & Akçay, 2016 ). While such a mechanism is highly likely, and indeed has been supported in some social systems, such as spotted hyenas, Crocuta crocuta (Ilany, Holekamp & Akçay, 2020 ), this model requires knowledge about relatedness and historical interactions, or long‐term relationships, that are not available in all study systems. In our burbil case study in Appendix S1 (Section 3.4.2 ) we develop two socially explicit agent‐based models that build on our spatially explicit model.…”
Section: Generative Reference Modelsmentioning
confidence: 99%
“…In addition to parental support, the offspring of adults higher in the hierarchy could receive greater third-party support from non-parents, here termed 'social support' (see section II.5b). It has been suggested that offspring in group-living species may inherit their parents' social associations (Goldenberg, Douglas-Hamilton, and Wittemyer 2016;Ilany and Akçay 2016;de Waal 1996; but see 25 Ogino, Maldonado-Chaparro, and Farine, 2021); recent work in spotted hyenas has demonstrated a strong correlation between parent and offspring social associations that persists for up to six years (Ilany, Holekamp, & Akçay, 2020), demonstrating the potential for offspring to inherit coalition partners. Such social inheritance of parental associations could occur simply via passive space-use processes -where offspring remain with their parents who tend to move in proximity to their affiliates, resulting in offspring and parental affiliates (or their offspring) forming associations (Ilany & Akçay, 2016).…”
Section: ) Parental Effects On Offspring Third-party Supportmentioning
confidence: 99%